The Impact of Financial Technology (Fintech) Peer-to-Peer Lending Literacy and Inclusion on MSME Financing Decisions in the Mandalika Special Economic Zone - Alpian Muhtarom, Zamroni; Andryan Girsang, Zefanya; Najib Roodhi, Mohammad; Dewi Kuntary Ibrahim, Isra; Safitri, Dhanny (Journal of Institution and Sharia Finance, 2025)
This study aims to analyze the influence of financial literacy and financial inclusion through peer-to-peer (P2P) lending fintech on the financing decisions of Micro, Small, and Medium Enterprises (MSMEs) in the Mandalika Special Economic Zone (SEZ). The research employs a descriptive quantitative method using Partial Least Squares (PLS) with a Structural Equation Modeling (SEM) approach, involving 210 MSME respondents. The findings indicate that both independent variables have a positive and significant effect on financing decisions. However, financial inclusion exerts a more dominant influence than financial literacy, as reflected in its higher t-statistics and path coefficients. These results suggest that ease of access to digital financial services plays a crucial role in strengthening MSME financing decisions. Therefore, enhancing financial literacy and promoting the use of inclusive financial technologies are expected to expand financing access and stimulate local economic growth.